Analysis of IMOD-Based Poetry Reading Ability in Grade V Students: Analisis Kemampuan Membaca Puisi Berbasis IMOD pada Siswa Kelas V SD - Safitri, Rina Eka; Fatayan, Arum (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Reading skills are a fundamental component of language learning in elementary education, particularly for developing students’ cognitive and affective abilities. Specific Background: Poetry, as a distinct literary form, demands specialized techniques for interpretation and expression, making it a challenging yet valuable medium in language instruction. Knowledge Gap: However, students often struggle with poetic comprehension and expression due to the lack of effective pedagogical strategies tailored to poetry reading. Aims: This study aims to analyze the implementation and effectiveness of the IMOD (Imitation Model) method in enhancing the poetry reading skills of fifth-grade elementary students. Results: Using a qualitative case study approach involving classroom observations, interviews, and documentation, the research found that IMOD significantly improved students' engagement and interpretative performance, especially for poems themed